2018
DOI: 10.1177/0003489418779414
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Internet Use Among Otolaryngology Patients

Abstract: Internet access was far from universal among this large cohort of otolaryngology outpatients. Head and neck cancer (HNC) patients report the least online access among all otolaryngology subspecialties. Providers should consider nonelectronic patient resources for older, more rural, less educated, and HNC patient populations as online/electronic methods of communication may not be accessible to these groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…29,30 Among patients who have an appointment with an Otolarngology – Head and Neck surgeon, up to 39% use the Internet to access health information related to their condition before their clinic visit. 31,32 Studies have shown that the use of online health information by patients can have a significant impact in the health care decision making process. 29,33,34 However, due to the lack of regulation and vast amount of resources available to patients online, quality control remains a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Among patients who have an appointment with an Otolarngology – Head and Neck surgeon, up to 39% use the Internet to access health information related to their condition before their clinic visit. 31,32 Studies have shown that the use of online health information by patients can have a significant impact in the health care decision making process. 29,33,34 However, due to the lack of regulation and vast amount of resources available to patients online, quality control remains a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The authors postulate that possibly traditional information sources come into the focus when the individual health is explicitly affected. However, and US American trial from 2018 [32] revealed that more than one third of ENT patients retrieve information on the internet about their health status prior to visiting a doctor.…”
Section: The Internet As Medical Information Medium For Advice-seekinmentioning
confidence: 99%
“…Also, the access and the significance of the internet for ENT patients has already been investigated several times. An increasing use of the internet could be observed, which in 2002 was reported with 45.5 % [41], while the most recently published report from 2018 mentioned 91.3 % [42]. One study directly compared two surveys from 2000 and 2006 and revealed a considerable increase in the use of the internet also for health-related issues [43].…”
Section: Development Of Internet Use For Retrieving Healthcare Informmentioning
confidence: 99%